A DESIGNED METHOD FOR 48-PULSE DIODE RECTIFIER WITH COUPLED THREE PHASE REACTOR - Kirthika, S.; Alageswari, P.; Kumar, R.Senthil (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper presents a designed methodology for power electronics, which converts AC into DC voltage with a system of three-phase coupled reactors which securesÂ consumption of the current. In order to reduce to ripples ,here pure inductor is used from the supply itself. Here eight diode bridge rectifier is also used to get 48 pulses then it will apply to the DC load.This work consists of simulation result, designed topology of a 2-kVA model of 48-pulse converter system. While converting 24 pulse converter to 48 pulse converter the power quality problems like harmonics and Total Harmonic distortion is greatly reduced. The main advantage of this converters is to reduce the consumption of the deformation power.HereÂ 48 pulse diode rectifier with couples three phase reactor is simulated using MATLAB/SIMULINK software.